2017
DOI: 10.1002/ptr.5927
|View full text |Cite
|
Sign up to set email alerts
|

Chebulinic Acid Isolated From the Fruits of Terminalia chebula Specifically Induces Apoptosis in Acute Myeloid Leukemia Cells

Abstract: Chebulinic acid, an ellagitannin found in the fruits of Terminalia chebula, has been extensively used in traditional Indian system of medicine. It has shown to have various biological activities including antitumor activity. The present study aims to investigate the cytotoxic potential of chebulinic acid in human myeloid leukemia cells. Interestingly, chebulinic acid caused apoptosis of acute promyelocytic leukemia HL-60 and NB4 cells but not K562 cells. In vitro antitumor effects of chebulinic acid were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…This method studies revealed that 0.712% w/w of chebulinic acid content in the composition of herbal powder, the assay of chebulinic acid was calculated according to Eq. (4) (Chhabra et al, 2017). The retention time observed for the authentic sample of chebulinic acid results was given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This method studies revealed that 0.712% w/w of chebulinic acid content in the composition of herbal powder, the assay of chebulinic acid was calculated according to Eq. (4) (Chhabra et al, 2017). The retention time observed for the authentic sample of chebulinic acid results was given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that incremental doses of CA induced concomitant cell death in MDA‐MB‐231 cells. Although, CA has previously been demonstrated to have cytotoxic properties against a variety of cancer cell lines namely leukemia, vascular smooth muscle cells, pancreatic cancer, prostate cancer, and osteosarcoma cell lines (Chhabra et al, 2017; Saleem, Husheem et al, 2002; Shi et al, 2008), our study extends anticancer activity of CA to highly metastatic cancer types and provides a molecular basis for its activity by identifying its ability to induce autophagy and downregulating SOD1 as putative molecular target. CA treatment induced significant cell death and reduced proliferative and metastatic characteristics in TNBC's.…”
Section: Discussionmentioning
confidence: 99%
“…MDA‐MB‐231 cell line was procured from American Type Culture Collection and cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS) with antibiotics and maintained in a humidified incubator with 5% CO 2 at 37°C. Isolation and validation of CA was performed as previously described (Chhabra et al, 2017). Stock of CA was prepared at the concentration of 50 mM in DMSO.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations